Pemanfaatan Biblio Konseling Sebagai Upaya Pencegahan Pelecehan Seksual Di Lingkungan Sekolah (Surakarta) (Prosiding Konseling Kearifan Nusantara (KKN), 2024)
Sexual harassment, as explained in the Big Indonesian Dictionary, can be defined as a form of discrimination based on harassing actions, which include insulting, degrading, or ignoring someone. Meanwhile, sexual elements in this context refer to matters related to aspects of sex or gender, or related to issues of sexual relations between men and women. Sexual harassment includes behavior or attention that is sexual, that is unwelcome, unwanted, and may cause harm to the victim of the harassment